A Smooth Shadow-Rate Dynamic Nelson-Siegel Model for Yields at the Zero Lower Bound - Daan Opschoor; Michel van der Wel (Tinbergen Institute, 2022)
We propose a smooth shadow-rate version of the dynamic Nelson-Siegel (DNS) model to analyze the term structure of interest rates during the recent zero lower bound (ZLB) period. By relaxing the no-arbitrage restriction, our shadow-rate model becomes highly tractable with a closed-form yield curve expression. The model easily permits the implementation of readily available DNS extensions such as time-varying loadings, integration of macroeconomic variables and time-varying volatility. Using U.S. Treasury data, we provide clear evidence of a smooth tran- sition of the yields entering and leaving the ZLB state. Moreover, we show that the smooth shadow-rate DNS model dominates the baseline DNS model in terms of fitting and forecasting the yield curve, while being competitive with a shadow-rate affine term structure model.
Keywords: E43; E47; C53; C58; G12; 330; Yield curve; zero lower bound; shadow-rate model; Nelson-Siegel curve